2000
DOI: 10.1128/jcm.38.10.3827-3829.2000
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Five Agar Media for Recovery of Fungi from Isolator Blood Cultures

Abstract: We studied the recovery of 1,270 fungal isolates from 176,144 Isolator blood cultures (0.72% positive) on bacterial and fungal media, under routine and differing incubation conditions. Except withHistoplasma capsulatum, chocolate agar incubated for only 3 days proved to be an excellent medium for the recovery of fungi from the Isolator system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…e 30-day follow-up CT showed that the right lung cavity was reduced, and the left lung fibrous foci existed (d). [15]. Even with the newer diagnostic methods, such as hemolytic precipitation and culture of Candida, the positive rate is not high enough.…”
Section: Discussionmentioning
confidence: 99%
“…e 30-day follow-up CT showed that the right lung cavity was reduced, and the left lung fibrous foci existed (d). [15]. Even with the newer diagnostic methods, such as hemolytic precipitation and culture of Candida, the positive rate is not high enough.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can be difficult to determine whether a positive culture from a non‐sterile site is attributed to colonization or active infection (10). Nonetheless, improvements in culture techniques, such as the development of lysis centrifugation, new formulations of culture media, and automated blood culturing and monitoring systems, have led to a higher frequency and a more rapid detection of Candida species from blood samples (13–16). Unfortunately, sensitivity remains low, with the rate of positive samples from patients with invasive candidiasis at approximately 50% (17, 18).…”
Section: Traditional Methods Of Diagnosing Fungal Infectionsmentioning
confidence: 99%
“…The sterile molten agar was poured inside the inoculated Petri dishes, swirled gently before allowing it to set. Culture plates were incubated at 25 o C for 72 hours [15]. Twenty-seven (27) yeasts were isolated from forty-three (n=43) milk samples cultured.…”
Section: Microbiological Analysis Of the Samples [14]mentioning
confidence: 99%